A Building Material Inventory Planning Using Always Better Control (ABC) and Economic Order Quantity (EOQ) - Irwan Sukendar (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
Langgeng Jaya is a retail business engaged in the sale of construction materials and building tools. TB. Langgeng Jaya has erratic demand historical data. So the problem arises how much inventory is needed. Building materials in TB. Langgeng Jaya is obtained from quite a lot of distributors or suppliers with different lead times for each company. Inefficient management results in problems in product inventory such as out of stock and excess stock of building materials being sold. To overcome this problem, the method used in this research is Always Better Control (ABC) and Economic Order Quantity (EOQ) analysis. The ABC method is used to classify a large number of product types into three groups, namely group A, group B, and group C. In this approach it results that those included in group A are 30 types of products with a monetary value percentage of 77.46%. group B there are 31 types of products with a monetary value of 12.57%, while for group C there are 89 types of products with a monetary value of 9.97%. Group A has a higher cumulative price percentage value than groups B and C which will later become the focus for further processing using the EOQ method. By using the EOQ (Economic Order Quantity) multi-item multi-supplier and single item single-supplier policies, this can reduce the costs incurred from ordering goods from suppliers. The results of the EOQ (Economic Order Quantity) method approach, namely the difference in costs incurred by the average company, are Rp. 1,192,537.